Knowledge, attitudes, and practice toward tuberculosis in high school students in Qingdao, China - Dai, Xiaoqi; Li, Shuo; Song, Song; Chen, Meng; Xu, Honghong; Li, Xuekui; Zhang, Menghan; Zhang, Huaqiang; Sun, Haiyan; Wang, Zhongdong (The Journal of Infection in Developing Countries, 2024)
Introduction: The purpose of this study is to assess the levels of knowledge, attitude, and practice (KAP) related to TB, and to analyze the differences among various demographic groups. Methodology: A total of 621 students enrolled in Qingdao High School, coming from high TB burden settings. The cross-sectional study was conducted from May to July of 2022. Participants completed an online questionnaire. Differences in knowledge and practice based on participant characteristics were analyzed using the Wilcoxon rank test and Kruskal-Wallis rank test. Group differences were assessed using a rank-based analysis of variance. Results: The mean percentage of correct answers for TB knowledge and practice was 82.09% and 83.25%, respectively. Grade Three students showed higher knowledge and practice scores than Grade One or Grade Two students (t = -3.9935, p = 0.0002, t = 3.4537, p = 0.0018. 8.58 vs 7.94, 8.58 vs 8.23. t = 3.4562, p = 0.0018, t = -2.8688, p = 0.0128. 1.78 vs 1.61, 1.78 vs 1.64). A significant majority (78.42%) of students expressed fear of being affected by TB. 49.28% of the students would support and help TB patients. 88.08% of participants had heard of TB, with 72.94% learning about it at school, mainly through visual aids like posters. Information was predominantly obtained from online sources (websites, microblogs, WeChat, etc.). Conclusions: It is recommended to develop a TB curriculum for lower-grade students to enhance awareness of TB prevention through various means, including the internet and social media.